L'Inspiration romantique de Gaspard de la Nuit - Leite, Guacira Marcondes Machado [UNESP] (My University, 2011)
In this work, we intend to show that Aloysius Bertrand in “Gaspard de la Nuit” drew the inspiration to his poems in prose from its nearest context: that one of French Revolution and the revolt of the spirit against everything which would impose an exaggerated materialism. Thus, in the middle of Enlightenment, there were those who went in search of “mysterious realities” and a “sense of mystery” that the pre-romantic literature in Britain and in Germany would express in its poetry. It is also in the 18th century that some works about the “Commedia dell‟arte” and caricature concede to the grotesque a significant part in the formation of art, extending it to the supernatural and the absurd.

Neste trabalho, queremos mostrar que Aloysius Bertrand foi buscar a inspiração para seus poemas em prosa de Gaspard de la Nuit no seu contexto mais próximo: o da Revolução Francesa e da revolta do espírito contra tudo o que lhe impunha um materialismo por demais exagerado. Assim, em pleno Século das Luzes, houve aqueles que partiram em busca de "realidades misteriosas" e de um "sentido do mistério" que a literatura pré-romântica na Inglaterra e na Alemanha iria exprimir em sua poesia. É no século XVIII, também, que algumas obras sobre a "commedia dell'arte" e a caricatura concedem ao grotesco uma parte significativa na formação da arte, estendendo-a ao sobrenatural e ao absurdo.
The romantic inspiration of Gaspard de la Nuit
Keywords: Aloysius Bertrand; Poem in prose; French poetry; Romanticism; Aloysius Bertrand; Poema em prosa; Poesia francesa; Romantismo